Comparative study of outcome between IAP versus WHO guideline for initial fluid bolus therapy in severely malnourished children with shock - Oza, Jaimin R.; Javadekar, Bakul B.; Zanzrukiya, Dipal M. (International Journal of Contemporary Pediatrics, 2023)
Background: Severe acute malnutrition is a major cause of mortality in children under 5 years of age in developing countries. Dehydration and Shock are the common serious complications of SAM and require cautious treatment. We carried out this study to compare 2 different guidelines given by WHO and IAP in patient of SAM with shock to compare their outcome and complications. Methods: A randomized controlled trial was conducted during January 2019 to October 2019 at tertiary care centre of central Gujarat. Total 40 patients were enrolled according to inclusion criteria and randomized into two groups equally, Group A (following WHO guidelines) and Group B (following IAP guidelines). Rehydration therapy was given accordingly and patients were assessed for improvement in shock, developing complications and outcome as discharge or death. Results: Out of 20 patients in each group, after bolus, not a single patient in group A showed improvement after 1 hour while in Group B 3/20 (15%) patients were improved. In Group A 8/20 (40%) and in Group B 12/20 (60%) patients showed improvement within 12 hours of bolus. In Group A 7/20 (35%) patients and in Group B 6/20 (30%) patients developed complication of fluid overload. In Group A 12/20 (60%) while in Group B 8/20 (40%) patients expired during the treatment. Conclusions: Rehydration therapy according to IAP guidelines showed better improvement in shock, less incidence of complications and better outcome as compared to WHO Guidelines in SAM patients, however no significant difference was achieved due to smaller sample size.